Actor-Network Dynamics in the Use of Carettochelys insculpta Eggs in South Papua: A Social Network Analysis Approach - Purnama Graha; Mirza Dikari Kusrini; Syartinilia Syartinilia; Richard Gatot Nugroho Triantoro (Jurnal Ilmu Pertanian Indonesia, 2026)
Carettochelys insculpta, a freshwater turtle with ecological importance in riverine systems and cultural value for local populations in South Papua, Indonesia, is the only remaining member of the Carettochelyidae family. Despite its protected status, egg collection is unsustainable and illegal due to poor governance ability and fragmented stakeholder cooperation. This study employed social network analysis to evaluate the interactions between egg harvesting and trade actors and suggest potential intervention locations. Egg collectors had the highest degree centrality, indicating extensive direct linkages; government players had strong proximity and betweenness centrality, uniting otherwise disparate groups; and brokers with high eigenvector centrality-controlled trade indirectly via links with other major actors. Modularity analysis revealed three actor clusters with stronger internal than external relationships, whereas MR-QAP results indicated non-random patterns driven by institutional linkages. Limitations include the extent of actor coverage, since peripheral stakeholders may not be fully represented, despite confirmation through literature and focus group discussions. Technical assistance for egg collectors, increased collaboration among actor groups, and regulatory measures that are consistent with traditional practices are among the recommendations made. The approach establishes a framework for integrating social and spatial data to detect governance gaps and prioritize solutions in species use management. Keywords: centrality metrics, cnservation strategy, ranching initiatives, turtle egg harvesting, wildlife use